The clinical significance of SNAIL, TWIST, and E-Cadherin expression in gastric mesentery tumor deposits of advanced gastric cancer - Haiyan Wu; Yanping Chen; Huimei Lin; Yanchang Xu; Zipei Guo; Zhixiong Li (Indian Journal of Pathology and Microbiology)
Objective: To explore the relationships among the epithelial to mesenchymal transition (EMT)-related factors (SNAIL, TWIST, and E-Cadherin) and clinicopathological parameters and gastric mesangial tumor deposits (TDs) in advanced gastric cancer (AGC) patients and their value in gastric cancer prognosis judgment. Materials and Methods: The data of 190 patients who underwent radical resection of ACG were analyzed retrospectively, including 75 cases of TDs (+) and 115 cases of TDs (-). The expression of EMT-related transforming factors Snail, Twist, and E-cadherin in the primary tumor, paracancerous normal tissues, and TDs was detected by immunohistochemistry. Results: SNAIL and TWIST were overexpressed in primary tumors and TDs, whereas E-Cadherin was down-expressed in primary tumors. SNAIL was correlated significantly with tumor differentiation, lymph node metastases, and TDs (P < 0.05); TWIST was correlated strongly with tumor location, lymph node metastases, and TDs (P < 0.05); E-Cadherin was correlated closely with tumor differentiation and lymph node metastases (P < 0.05). Kaplan-Meier curves showed that SNAIL expression was correlated with DFS (P < 0.05), and TWIST expression was correlated with OS (P < 0.05). Tumor differentiation, lymph node metastasis, and TWIST expression were prognostic-independent risk factors of AGC patients (P < 0.05). Conclusion: The occurrence and development of gastric cancer and the formation of TDs may be related to EMT, analyzing the expression of EMT-related transforming proteins may be helpful to judge the prognosis of gastric cancer.